Molecular Synchronization Enhances Molecular Interactions: An Explanatory Note of Pressure Effects - Munenori Numata; Chisako Kanzaki (Crystals, 2018)
In this study, we investigated a unique aspect of the supramolecular polymerization of tetrakis (4-sulfonatophenyl) porphyrin (TPPS), a self-assembling porphyrin, under non-equilibrium conditions by subtracting the effects of back-pressure on its polymerization. We focused on the enhanced self-assembly abilities of TPPS under a process of rapid proton diffusion in a microflow channel. Rapid protonation caused synchronization of many sets of protonation/deprotonation equilibria on the molecular scale, leading to the production of many sets of growing suparmolecular spices. Pressure effects in the microflow channel, which could potentially promote self-assembly of TPPS, were negligible, becoming predominant only when the system was in the synchronized state.